Analysis of Company Size in Strengthening The Influence of Financial Performance on Company Value - Reschiwati, Reschiwati; Eugensia Sawu (Jurnal Manajemen dan Perbankan (JUMPA), 2024)
This research aims to analyze and obtain empirical evidence regarding the influence of financial performance as proxied by liquidity, probability and leverage on company value which is strengthened by company size. The population in this research is manufacturing companies registered on the IDX in 2017- 2022, namely 56 companies. By using purposive sampling, the number of observations was 102 companies from 17 companies. The data was processed using software using eviews 13 software. The novelty in this research is the measurement of the company size variable which is a moderating variable that uses categories, namely small, medium and large companies based on the provisions of OJK No. 53/POJK.04/2017. The research results show that only leverage influences the firm value of the three dependent variables. Company size is not proven to strengthen the influence of financial performance on company value. Company size is a moderating variable that is a moderation homolizer. This research means that investors can consider their investment decisions and can see directly the financial performance, especially the level of leverage, without paying attention to the size of the company.